Can ethical texts achieve clarity?: whistleblowing texts in the UK banking sector and the ethical clarity framework - Hornby, Elizabeth (Journal of business ethics, 2025)
The importance of clarity in the effective embedment of corporate ethical cultures is well established. But if we are concerned with the efficacy of corporate cultures, we must also be concerned with how clearly they are communicated. The main way in which ethical cultures are communicated to employees is in ethical texts, such as codes of conduct and ethical policies and procedures. If these ethical texts do not achieve clarity, they risk undermining rather than embedding the ethical cultures that they seek to document. But, can ethical texts achieve clarity? This article builds on Kaptein’s Corporate Ethical Virtues Model by extending the corporate ethical virtue of clarity to the formal context of ethical texts and offers valuable insights into how and why clarity is enabled or obstructed in such texts. A practical tool, the ethical clarity Framework, is developed for the analysis and mapping of clarity in ethical texts and then applied in the exemplar setting of whistleblowing texts in the UK banking sector. The findings suggest that the drivers for inconsistency and ambiguity in ethical texts lie in the difficulty of naming and framing ethical concepts, incoherence in the external landscape, and the need to satisfy the competing interests of multiple actors. The article concludes that ethical texts may not be able to achieve clarity and should, perhaps, not attempt to do so.